Factors of low back pain among nurses in Mahasarakham Hospital - Khotchakhote, Juthamart (Journal of Public Health Nursing, 2023)
This cross-sectional analytic study aimed to investigate the prevalence of low back pain among nurses in Mahasarakham Hospital. 204 nurses participated in this study. Data were collected by questionaries, and assessment of ergonomic risk by Standardized Nordic Questionnaire, musculoskeletal symptoms perception and prevention musculoskeletal symptoms behavior. Descriptive statistics were used to describe the characteristics, and multiple logistic regression analyses at 95% confidence interval of odds ratio (OR) were used to identify low back pain risk factors. The prevalence of low back pain during the last 12 months period was 52.94. Ergonomic risk assessment by Standardized Nordic Questionnaire were low back, shoulder and neck are the most local of musculoskeletal symptoms. The related factors to low back pain were frequency of patient transfer > 5 times/shift (OR = 0.46, 95% CI = 1.25 – 15.60). Physical exercise prevents low back pain (OR = 4.68, 95% CI = 0.24 - 0.90). Therefore, there should be improved health behavior and working conditions, the working posture of the worker. Training courses in manual lifting and material handling were needed for nurses to prevent musculoskeletal symptoms.